"Bath Salt" Use and Beliefs about Use among Electronic Dance Music Attendees. Issue 5 (20th October 2018) - Palamar, Joseph J.
ABSTRACT: Use of synthetic cathinones ("bath salts") has been associated with tens of thousands of emergency department visits. Few surveys, however, query use. Research on "bath salt" use is needed, especially in high-risk populations, to inform prevention and harm reduction efforts. A total of 933 adults (ages 18–40) were surveyed entering electronic dance music (EDM) parties in New York City in 2017. Lifetime use of 22 different synthetic cathinones was queried, and agreement with four statements about "bath salts" was also assessed. Prevalence and correlates of self-reported "bath salt" use was examined as well as correlates of beliefs about "bath salts." An estimated 3.5% of EDM attendees have knowingly used "bath salts." Almost half (46.7%) believe "bath salts" are more harmful than MDMA, 30.1% believe "bath salts" have turned users into cannibals, 30.0% believe "bath salts" are sometimes found in Molly, and 14.9% believe they might have unknowingly used "bath salts." Males, those earning <500 per week, and those with a college degree were at higher risk for use. Believing "bath salts" have turned users into cannibals, however, was protective against use. Findings suggest the need for more accurate information (e.g., regarding drug effects) on this large and heterogeneous group of compounds.